2019
DOI: 10.1534/genetics.118.301874
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid/Pkh1/2-TORC1/Sch9 Signaling Regulates Ribosome Biogenesis in Tunicamycin-Induced Stress Response in Yeast

Abstract: Reduced ribosome biogenesis in response to environmental conditions is a key feature of cell adaptation to stress. For example, ribosomal genes are transcriptionally repressed when cells are exposed to tunicamycin, a protein glycosylation inhibitor that induces endoplasmic reticulum stress and blocks vesicular trafficking in the secretory pathway. Here, we describe a novel regulatory model, in which tunicamycin-mediated stress induces the accumulation of long-chain sphingoid bases and subsequent activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
(95 reference statements)
1
14
0
Order By: Relevance
“…This is also consistent with the model that tricalbins play a role in preventing the accumulation of toxic lipids such as ceramide, which causes ER stress. It is noteworthy that tunicamycin treatment appears to impair the transport of ceramides between the ER and the Golgi ( Pittet et al., 2006 ; Yabuki et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with the model that tricalbins play a role in preventing the accumulation of toxic lipids such as ceramide, which causes ER stress. It is noteworthy that tunicamycin treatment appears to impair the transport of ceramides between the ER and the Golgi ( Pittet et al., 2006 ; Yabuki et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding also demonstrated that GAS1 -overexpressing yeast cells displayed significantly the ER stress sensitivity under the low-Tm-concentration stress. One possibility for this result is that Tm, as an N-linked glycosylation inhibitor, can block the glycosylation of the overexpressed Gas1 protein, resulting in the accumulation of misfolded protein within the ER and ultimately leading to cell death [32, 33]. Thus, our findings indicated that Gas1p is involved in regulating ER stress responses.…”
Section: Resultsmentioning
confidence: 81%
“…This protein is a glutamine sensor that acts independently of the GSE/EGO complex to activate TORC1 [ 36 ]. Compelling, TORC1 has been linked to endocytosis [ 37 ], ribosome biogenesis [ 38 ], and the HAP complex [ 39 , 40 ] and therefore TORC1 may represent a second central node in polygodial resistance. The TORC1 node is closely linked to the UBI4 node since ubiquitin was shown to exert a positive effect on TORC1 by preventing degradation of the TORC1 subunit Kog1 under stress conditions [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%